Pengaruh Motivasi dan Kinerja Pelatih Teater terhadap Percaya Diri Anggota - Hary Murcahyanto; Riyana Rizki Yuliatin; Apriwulan Adhari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The aim of the study was to determine the influence of the trainer's motivation and performance on the self-confidence of theater extracurricular members. This research is quantitative research using the Ex-Post-Facto method. The sample in this research was all members of the theater extracurricular, totaling 20 students from grades VII, VIII and IX. The instrument used is a questionnaire sheet. Measurement using a Likert scale. The result of the research is that the trainer's motivation cannot affect the self-confidence of theater extracurricular members. The trainer's performance does not have a direct influence on the self-confidence of theater extracurricular members. The self-confidence of theater extracurricular members cannot be influenced by the motivation and performance of theater extracurricular trainers. This shows that a member's self-confidence which includes independence, confidence in abilities, a sense of courage to argue, and a normal attitude, as well as not being awkward in interactions cannot be influenced by the trainer's own motivation and performance. This conclusion is that the trainer's motivation influences the trainer's performance; The trainer's motivation has no effect on the self-confidence of theater extracurricular members; the trainer's performance has no effect on the confidence of the theater extracurricular members. Keywords: Coach, Extracurricular, Motivation, Performance, Self Confidence